2021
DOI: 10.1177/20420986211021230
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol-induced hiccups: a case–noncase study in the European pharmacovigilance database

Abstract: Background: Hiccups are usually benign and self-limiting, but can sometimes be persistent. If left untreated, they can provoke severe discomfort, and even death. Hiccups can be idiopathic, organic, psychogenic, and caused by drugs. Although some case reports have suggested a possible association between tramadol and hiccups, to our knowledge, no study has analyzed this possible relationship. The aim of this study was to analyze whether a disproportionate number of cases of hiccups are reported for tramadol in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Employing methodology published previously, 17 The EUADR database was searched for products containing ciprofloxacin, trimethoprim, sulfamethoxazole (co-trimoxazole), amoxicillin, and nitrofurantoin. Results were screened to those reported by healthcare professionals only and refined by renal.…”
Section: Methodsmentioning
confidence: 99%
“…Employing methodology published previously, 17 The EUADR database was searched for products containing ciprofloxacin, trimethoprim, sulfamethoxazole (co-trimoxazole), amoxicillin, and nitrofurantoin. Results were screened to those reported by healthcare professionals only and refined by renal.…”
Section: Methodsmentioning
confidence: 99%
“…In a review of the French Pharmacovigilance Database, Bagheri et al (18) found that opioids accounted for 6% of the 53 cases of drug-induced hiccups reported in France between 1985 and 1997 (three cases in 12 years). In a case-noncase study conducted on the European Pharmacovigilance Database and published in 2021, García et al (19) showed a statistical association between tramadol and hiccups. Their data also suggest that tramadol is more often related to hiccups than other opioids.…”
Section: Literature Evidence For Opioid-related Hiccupmentioning
confidence: 99%
“…Globally, the use of tramadol has increased rapidly over the past few decades, resulting in a 22.8% growth between 2012 and 2015 in the United States, making tramadol one of the most prescribed opioids with excessive expectations of safety and low abuse liability [ 5 , 6 ]. However, concomitant use of medications that increase serotonin level, such as fluoxetine, venlafaxine, or overuse of tramadol, has been found to be associated with serious AEs, such as serotonin syndrome or seizures [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the FDA, their new warning in 2017 was based on nine cases of respiratory depression, including three deaths reported in children under 18 years of age between 1969 and 2016 to the FDA Adverse Event Reporting system [ 16 ]. Several pharmacovigilance studies assessing tramadol have been reported [ 5 , 26 ]; however, no previous study has investigated tramadol-related respiratory depression using a VigiBase. Therefore, it is important to evaluate the risk and factors for respiratory depression of tramadol based on a large, real-world database.…”
Section: Introductionmentioning
confidence: 99%